Two Linguistic Case Studies of the Craft of Songwriting: 'Imagine' and 'Like a Rolling Stone' - Hewett, Matthew R (Lingua Frankly, 2017)
The songs “Imagine” and “Like a Rolling Stone”, written by John Lennon and Bob Dylan respectively, demonstrate the musicians' acute awareness of the expressive force which saturates particular grammatical constructions, lexemes, tense/aspect combinations, and other linguistic phenomena. Lennon and Dylan brandish their linguistic savvy by connecting with their audiences, albeit in fundamentally different ways. This paper seeks to highlight some commonalities and differences between how two of the most famous singer/songwriters of the late 60s and early 70s both connected with and manipulated their listenership. Furthermore, it seeks to demonstrate how a close linguistic analysis contributes to the general understanding of the momentous socio-cultural responses these songs elicited in popular culture. The methodology involves a close investigation of linguistic forms, including line-by-line analyses and comparisons between the two writers.